Features of psychosocial functioning of patients with combat traumatic brain injury of varying severity: analysis of interconnection - I. Chernenko; M. Markova (Journal of Education, Health and Sport)
Relevance. The full-scale invasion of Ukraine by the Russian Federation has had a signifcant impact on the daily lives of the country's civilian population, radically undermining their sense of security and causing constant stress, the psychological consequences of which are dangerous for both adults and children. The hostilities have in some places turned into a hyper-extreme situation for certain groups of the population. The internal tension and discomfort they cause exceed human capacity. We often see violations of international humanitarian rights and the Geneva Conventions, which leads to a situation of general distrust and frustration. We can distinguish socio-psychological, physical, economic and medical factors that affect the health of the population in wartime. During war, social problems arise that are directly related to the emergency. The purpose: to compare the peculiarities of psychosocial functioning of patients with combat traumatic brain injury of varying severity in order to understand the basis for differentiating therapeutic and rehabilitation measures for this contingent. Materials and methods. The features of the severity of psychopathological symptoms, including depressive, anxiety and post-traumatic, were studied in 350 patients with TBI of varying severity due to the action of a blast wave, taking into account the time elapsed since the injury. For this purpose, in each group according to the severity of TBI (mild (145 patients), moderate (125 people), severe (80 patients)), we identified three subgroups. Thus, the following groups of subjects were formed in the study: patients with mild TBI and the duration from the moment of injury to our examination from 6 to 12 months, numbering 35 patients; patients with mild TBI and the duration from the moment of injury from 1 to 3 years, numbering 60 patients; patients with mild TBI and the duration from the moment of injury from 4 to 7 years, numbering 50 patients; patients with moderate TBI and duration from the moment of injury from 6 to 12 months, in the number of 30 patients; patients with moderate TBI and duration from the moment of injury from 1 to 3 years, in the number of 45 patients; patients with moderate TBI and duration from the moment of injury from 4 to 7 years; patients with severe TBI and duration from the moment of injury from 6 to 12 months, in the number of 20 patients; patients with severe TBI and duration from the moment of injury from 1 to 3 years, in the number of 30 patients; patients with severe TBI and duration from the moment of injury from 4 to 7 years. The study of the features of psychosocial functioning was carried out using the methodology of the study of socio-psychological adaptation of K. Rogers - R. Diamond, the method of "Coping-test" by R. Lazarus and the Multidimensional Scale of Social Support. Results and discussion. The study of socio-psychological adaptation is important for understanding the complex picture of changes in the psychosocial functioning of patients with TBI. To understand the relationship between the severity of social and psychological adaptation and the intensity of psychopathological symptoms, we conducted a correlation analysis between these parameters. To do this, the study of the features of anxiety, depression, and posttraumatic symptoms was conducted using the Symptom Check List-90-Revised (SCL-90-R).  Conclusions. It should also be noted that lower scores in patients with more severe TBI may also be associated with a subjective pessimistic perception of their own social interaction, inherent in patients with depressive and posttraumatic manifestations, which are significantly more pronounced in patients with more severe TBI.